The effects of dexamethasone on α-fetoprotein and albumin synthesis in cultured hepatoma 7777 cells. Issue 10 (October 1982) - Schwartz, Charles E.; Burkhardt, Anne L.; Huang, Dao-Pei; Chiu, Jen-Fu
Abstract : Dexamethasone inhibits α-fetoprotein (AFP) synthesis, and stimulates albumin synthesis, in cultured hepatoma 7777 cells. These changes are due to a decrease in AFT-mRNA, and an increase in albumin-mRNA, in cells.